The role of inflammatory bowel disease nurses for patients on biologic therapy during the COVID-19 pandemic. (2nd March 2022) - Napolitano, Daniele; Galasso, Linda; Privitera, Giuseppe; Morana, Giuseppe; Bardelli, Arianna; Sinatora, Rita; Onidi, Maria Francesca; Lombardi, Maria Teresa; Orgiana, Nicoletta; Amatucci, Valeria; Strazzeri, Martina; Schiavoni, Elisa; et al.
Abstract : Background: During the COVID-19 pandemic, many inflammatory bowel disease (IBD) centres had to reorganise their work, and multidisciplinary teams, including IBD nurses, have had to try to deliver services to patients as safely as possible. Aims: This survey aimed to assess the thoughts, opinions and feelings of IBD patients on biologics regarding the efforts of IBD nurses to organise care during the COVID-19 pandemic. Methods: An evaluation survey based on an anonymous questionnaire was distributed to IBD nurses in five Italian IBD centres, in parallel. Findings: Of 306 participants, 55.6% had Crohn's disease and 44.4% had ulcerative colitis. Most (79.1%) were aware of the specialist IBD nurse role, and 75.8% could distinguish it from generalist nurses. Of patients, 99.7% felt IBD nurses were competent to care for their condition and 91.2% felt that IBD nurses could provide valid scientific information. Meanwhile, 81.4% had a good or excellent relationship with their IBD nurse. Patients reported that most nurses wore personal protective equipment (94.4%), promoted self-care (91.8%), asked about presence of fever or cough (84.3%), asked about patient health status (83.7%) and covered pandemic safety and social distancing rules (69.3%), but fewer spoke about patient mood (44.4%) or relevant benefits, rules and exemptions (26.8%). Most participants (77.8%) faced pandemic-related issues for infusions. Nearly all (97.4%) knew immunosuppressed people were vulnerable to COVID-19, but only 42.8% spoke to their nurse about it. Some 61.8% of patients were concerned about COVID-19, but only 39.2% raised this with the IBD nurse. However, many more patients spoke to a nurse about concerns regarding biologics (41.8%) and worsening IBD symptoms (46.4%) in the pandemic than the actual number experiencing these issues (13.7% and 4.3%, respectively). Conclusion: The results show that IBD patients appreciate the role of the specialist nurse in their care.